2022
DOI: 10.1080/07853890.2022.2147991
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of linked colour imaging versus white light imaging for early gastric cancers: a prospective, multicentre, randomized controlled trial study

Abstract: Background Linked colour imaging (LCI) is a novel new image-enhanced endoscopy (IEE) technology that produces bright and vivid images. The aim of this study was to assess the ability of LCI to improve the diagnostic accuracy of early gastric cancer (EGC) relative to white light imaging (WLI). Materials and methods We performed this study on patients undergoing screening endoscopy from 12 medical institutions in China. Patients were randomly assigned to receive WLI follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Subsequent studies comparing LCI and WLI for the detection of neoplastic lesions also showed the superiority of LCI. 7,8 Subanalysis proved that LCI enhanced neoplastic visibility with high frequency and showed a significant color difference between neoplasms and the surrounding non-neoplastic mucosae compared with WLI in stomach. 9 In the present study, we used data from the LCI-FIND trial to evaluate the diagnostic performances of WLI and LCI for gastric cancer according to H. pylori infection status.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequent studies comparing LCI and WLI for the detection of neoplastic lesions also showed the superiority of LCI. 7,8 Subanalysis proved that LCI enhanced neoplastic visibility with high frequency and showed a significant color difference between neoplasms and the surrounding non-neoplastic mucosae compared with WLI in stomach. 9 In the present study, we used data from the LCI-FIND trial to evaluate the diagnostic performances of WLI and LCI for gastric cancer according to H. pylori infection status.…”
Section: Discussionmentioning
confidence: 96%
“…The LCI‐FIND trial 4 revealed that LCI can detect neoplastic lesions in the upper gastrointestinal tract (i.e., pharynx, esophagus, and stomach) 1.67 times more significantly compared to WLI. Subsequent studies comparing LCI and WLI for the detection of neoplastic lesions also showed the superiority of LCI 7,8 . Subanalysis proved that LCI enhanced neoplastic visibility with high frequency and showed a significant color difference between neoplasms and the surrounding non‐neoplastic mucosae compared with WLI in stomach 9 .…”
Section: Discussionmentioning
confidence: 98%